2007
DOI: 10.1682/jrrd.2006.05.0047
|View full text |Cite
|
Sign up to set email alerts
|

Residual-limb quality and functional mobility 1 year after transtibial amputation caused by vascular insufficiency

Abstract: Abstract-This study identified which residual-limb quality factors are related to functional mobility 1 year after transtibial (TT) amputation. A group of 28 TT amputees were evaluated with respect to their functional mobility (Prosthesis Evaluation Questionnaire [PEQ], Locomotor Index, Timed Up and Go test). The general (Chakrabarty score) and bony (tibial length, relative fibular length) residual-limb quality factors were assessed. An increase in general residual-limb quality (Chakrabarty >60) was correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…A tibial length of 12 to 15 cm from the knee joint line correlated with a better functional outcome than shorter tibial lengths. Surgical technique and attention to the residual limb length ensures a more likely good functional outcome after TTA (29). In a high quality article, Suckow et al reported TTA and transfemoral amputee (TFA) patients were equally likely to ambulate independently or with assistance (within groups) at hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…A tibial length of 12 to 15 cm from the knee joint line correlated with a better functional outcome than shorter tibial lengths. Surgical technique and attention to the residual limb length ensures a more likely good functional outcome after TTA (29). In a high quality article, Suckow et al reported TTA and transfemoral amputee (TFA) patients were equally likely to ambulate independently or with assistance (within groups) at hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Past findings suggest that ambulation ability in amputees was positively influenced by a greater number of years since amputation, but negatively influenced by age. 22 Furthermore, Arwert et al 23 reported that residual limb length is of significant influence in ambulatory activity in amputees. Thus, in this study, we hypothesize that (1) SAI during stair ascent in TFAs will be correlated with both age (negatively) and time since amputation (positively) and (2) SAI will be positively correlated with residual limb length.…”
mentioning
confidence: 99%
“…After any type of amputation, the physician will usually propose the idea of a prosthesis; however, to achieve a good functional outcome, the work of the professionals, including those providing psychological support, must be well-coordinated and managed appropriately. In addition, patients receiving a prosthesis must be carefully selected [12].…”
Section: Introductionmentioning
confidence: 99%